Examining perceived organizational politics among Indian managers: Engagement as mediator and locus of control as moderator. Issue 3 (11th July 2016) - Agarwal, Upasna A.
Abstract : Purpose: This paper aims to test the effects of perception of organizational politics (POPS) on work outcomes–work engagement, innovative work behaviour and turnover intention. Mediating role of work engagement and the moderating role of locus of control (LOC) on perceived organizational politics–outcome (innovative work behaviour and turnover intention) relationship was investigated. Design/methodology/approach: Data were gathered from a sample of 302 full-time managerial employees in India. Results suggest that perceived organizational politics is significantly related to intention to quit and innovative work behaviour, and this relationship is partially mediated by work engagement. LOC moderates the organizational politics–work outcomes (work engagement and innovative work behaviour) relationship. Findings: The current research demonstrates that availability of a work environment, where there are unfair decisions, nepotism and favoritism, is an impediment to engagement, innovative work behaviour and retention of managers. It behooves of top management therefore focusing on reducing POPS and subsequent deficits in motivation by providing clear feedback regarding which behaviours their organization desires. Research limitations/implications: The study focused on POPS as reported by the employees and not on actual political behaviours. As the study did not cover all sectors, the results of this study should be interpreted with caution. Originality/value: The study extended the current research stream of perceived organizational politics research to one of the underrepresented developing Asian countries, India. The study also contributes in terms of its sample characteristics. Managerial employees working across different sectors, served as the setting of our empirical study.